Combating Spatial Praxis in I am Malala by Malala Yousafzai - VISMAYA.K.B,; PURUSHOTHAMAN , KAVYA (International Journal of Psychosocial Rehabilitation, 2020)
Spatial practices and perceptions are influenced by Space, which is a social item, or a perplexing social development. Society is spatially constructed and space is socially built. The objective of this paper is to dissect various spaces in Malala yousafzai’s autobiography I am Malala through the use of spatial theory and it additionally attempts to demonstrate that space isn't simply found by people and involved, however in the process it is changed and furthermore it likewise examines that space isn't only the spot of contention, yet an object of battle itself. This paper additionally endeavors to investigate how a social space is accomplished through different political and economic methods.